Relationship between Facebook and body esteem comparing college women - Hau, Greta; Molly, Crabb (University of Wisconsin--Stout. Research Services, 2014)
As of March 2013, Facebook recorded having 1.11 billion active members worldwide (Associated Press, 2013). Research reveals a staggering amount of college students are users of Facebook. Considering Facebook’s prevalence in the lives of young people, it is essential to understand how Facebook affects our society. The purpose of this study was to examine the relationship between Facebook and body esteem and compare this relationship between college freshmen and senior women. This nonrandom pilot study surveyed 106 college women at a west-central Wisconsin university. The method used was a crosssectional research design. We predicted that Facebook would negatively affect body esteem in young women when users utilized the site for social comparison among Facebook friends. We also predicted that there would not be a difference between college freshmen and senior women when looking at the relationship between Facebook and body esteem. Due to our research comparing college women based on academic status, survey data was statistically analyzed using cross-tabulations, mean comparisons, independent t-tests, and a Cronbach’s Alpha reliability analysis. Results showed mixed support for both hypotheses. Implications for those working with college women include raising awareness on possible effects of Facebook on body esteem, and providing tips for healthy usage of Facebook. Future research would benefit from a large, randomized national and global sample, and qualitative interviews to capture the lived experience of those surveyed.
Research article with tables.
Keywords: body esteem; college women; social comparison theory; Facebook; Women--United States--Identity; Feminine beauty (Aesthetics)--United States; Women college students; Body image; Facebook (Electronic resource); Social comparison